Redescription of Bakuella (Bakuella) marina Agamaliev and Alekperov, 1976 (Protozoa, Hypotrichia), With Notes on Its Morphology, Morphogenesis, and Molecular Phylogeny - Zhu, Rong; Zhang, Qi; Tang, Lan; Zhao, Yan; Li, Jingbao; Li, Fengchao (Frontiers in Microbiology, 2022)
Because the original description of B. (Bakuella) marina, type of the genus, is only based on protargol-impregnated specimens, one of the important living features, namely the presence/absence of cortical granules remains unknown so far. In the present work, a detailed investigation of a Chinese population of B. (Bakuella) marina is carried out using the integrated approaches, and the live morphology, ontogenesis and molecular information of B. (Bakuella) marina are presented for the first time. The infraciliature of this population corresponds perfectly with that of the original description. The in vivo observation indicates that B. (Bakuella) marina possesses colorless cortical granules. The most prominent morphogenetic feature of B. (Bakuella) marina is that the parental adoral zone of membranelles is completely replaced by the newly formed one of the proter. Molecular phylogenetic analysis based on small subunit ribosomal gene (SSU rDNA) shows that five Bakuella species are clustered with the species from other six Urostylid genera, namely Anteholosticha, Apobakuella, Diaxonella, Holosticha, Neobakuella and Urostyla. The monophyletic probabilities of the family Bakuellidae, genus Bakuella, subgenus B. (Bakuella) and subgenus B. (Pseudobakuella) are rejected by the approximately unbiased (AU) test. This study further shows that the family Bakuellidae, genus Bakuella and subgenus B. (Bakuella) are all non-monophyletic groups. In order to establish a reasonable classification system, the information on molecular and morphogenesis of more Bakuellids and its related species is urgently needed.